Tunnel Fenestration of the Mandibula after Unsuccessful Post Traumatic Treatment: A Case Report of the One Year Follow-Up - Peter Gillner; Richard Mosch; Constantin von See (MDPI AG, 2023)
Particularly severe cases with tunneled defects are rarely reported and are described only in a few case reports. This case report describes the treatment of a tunnel fenestration in the lower central jaw after unsuccessful endodontic treatment following trauma of incisors 31 and 41 over the course of six years, which led to the development of an internal granuloma and a radicular cyst in the lower jaw. The patient presented with a 2.67 cm3 radicular cyst displacing the surrounding tissue at regio 31 and 41, which resulted in a tunnel-like bony defect. Endodontic treatment and periapical root tip resection on teeth 31 and 41 with cystectomy, and with a 12 month follow-up, were successful in the healing of the bone defect. The preserved teeth received lithium disilicate crowns for definite restoration one year postoperatively. This treatment can be an option for the therapy of large cysts.